Pengembangan desa kemuning sebagai objek wisata minat khusus industri teh - Sariyanti, Sariyanti; , Indrawati., ST., MT; , Rini Hidayati., ST., MT (2016)
Tourist village is the development of the village into a tourist area with the potential of the village. Special tour interest is a form of travel, where tourists or visiting a temapt because it has a special interest or motivation on a type of object or activity that can be found or made at that location. By developing the village into a tourist village without compromising the character of the village itself is expected to increase economic income people and develop into independent village. In the district there is a popular tourist Karanganyar to foreign countries which are Sondokoro, Tawangmangu, Tea Garden, Sukuh and Cetho tample. Tawangmangu sub-district and District Ngargoyoso a district that is planned to be developed into a tourist area nature. Based on data from the 2014/2015 tourists in Tawangmangu decreased compared to the previous year is different with tourists in District Ngargoyoso the increased number of tourists. One of the increase in tourists in Ngargoyoso influenced by the emergence of a tea jamming Ndoro Dongker and Balai Branti serving tea as the main menu.Myrtle village known for its vast expanse of tea plantations and green. Tea production until now still running are processed by the tea factory of Dutch heritage (PT. Rumpun Sari I). The majority of people work Myrtle are farmers, entrepreneurs, civil servants and laborers. In the village of Myrtle developing home industry processed tea is traditionally by people around, there are three (3) home industry. From the description above can be concluded that the development of the Myrtle village as a tourist attraction of special interest to be one of the tea industry to offer the Myrtle community and society to introduce tea in wide circles. In addition to that it is an effort to improve the economy of rural communities to develop into independent and creative economy.